MODEL DAN FORMULASI DANA ALOKASI UMUM NAGARI (DAUN) UNTUK MENGATASI KETIMPANGAN FISKAL NAGARI (STUDI KASUS DI KABUPATEN PADANG PARIAMAN SUMATERA BARAT) - Adli Adli (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
This research uses the term Dana Alokasi Umum Nagari (Henceforth DAUN), general allocation fund for village as the replacement of the term village block grant. This research especially aims to solve tree major problems in DAUN policy, namely allocation, distribution, and the problem of priority DAUN program for the improvement of Nagari. This research uses case study approach that took place in Padang Pariaman West Sumatera.There are two data categories used in this research. First the data about stakeholders perception. The data gained through questionnaire that include 22 respondents selected through purposive sampling. Second, the data about the characteristic of Nagari that explain about the need and ability of Nagari in managing its governance. This secondarily data was collected from documentary study of Nagari.By using analytic hierarchical process (AHP) in analyzing the data, this study found, first the proportional fund for regency and Nagari was 86 : 14. Second compared with its fiscal capability the fiscal need dimension showed 59% in the formulation of the DAUN. Third, the first priority DAUN program was the improvement of Nagari infrastructure, the last priority was the improvement of Nagari economic affairs